Which immigrants should be naturalized? Which should be deported? Evidence from a survey experiment in Cote d'lvoire - Cogley, Nathaniel Terence; Doces, John Andrew; Whitaker, Beth Elise (Political Research Quarterly)
Experimental studies on immigration attitudes have been conducted overwhelmingly in Western countries and have focused on immigrant admission and naturalization, neglecting deportation as a possible outcome. In a survey experiment in Côte d Ivoire, where immigrants represent more than one-tenth of the population, we randomized attributes of hypothetical immigrants to determine which factors influenced respondents support for naturalization or deportation compared with staying in the country without citizenship. Support for naturalization was shaped by several expected economic and social attributes, while deportation preferences were influenced primarily by the immigrant s legal status and level of savings. Cultural proximity produced mixed results, with respondents less likely to support the naturalization of immigrants from neighboring African countries but also less likely to deport immigrants with whom they shared a religious faith. Finally, respondents were more likely to support the naturalization of immigrants who planned to vote if granted citizenship, especially when they were of the same religion as the respondent, indicating a degree of electoral calculation in a context where voting patterns are associated with religious identities. Together, these findings suggest that citizen preferences for naturalization and deportation are influenced by somewhat different factors, a possibility that warrants further testing in other contexts. - Reproduced.